2019
DOI: 10.1088/1757-899x/673/1/012135
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shear rate in high shear mixing process on the structure of cassava starch granule and reducing sugar product

Abstract: Cassava starch is one of the biopolymers which can be degraded to many useful products such as reducing sugar, non-reducing sugar and modified starch. However, it has a solid granule structure that can inhibit its degradation process. High shear mixing (HSM) is a well-known method for dissolving biopolymers. Shear effect of HSM created by a narrow slit between rotor and stator which can be increased by the increase of rotational speed. By increasing its shear effect, HSM is able to cut the glycosidic bond of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…These conditions enabled some amount of water to penetrate the granule structure and made the granule swell. This was supported by a study published previously, [ 16 ] which showed that the average granule size increased from 49.05 to 181.3 nm owing to the effect of the HSM process. Although the process created a large shear force, it was insufficient to provide remarkable results in changing the morphology of the granule shape.…”
Section: Resultssupporting
confidence: 85%
“…These conditions enabled some amount of water to penetrate the granule structure and made the granule swell. This was supported by a study published previously, [ 16 ] which showed that the average granule size increased from 49.05 to 181.3 nm owing to the effect of the HSM process. Although the process created a large shear force, it was insufficient to provide remarkable results in changing the morphology of the granule shape.…”
Section: Resultssupporting
confidence: 85%